Consumer awareness towards advertising tools on Gradhitz package done by Bank Islam Malaysia Berhad (BIMB) / Marya Elena Rayen Abdul Aziz Rayen - Abdul Aziz Rayen, Marya Elena Rayen (Faculty of Business Management, 2006)
The research is entitled "Consumer Awareness towards Advertising Tools on Gradhitz Package Done by Bank Islam Malaysia Berhad (BIMB)". The objectives of the study are, to examine the level of consumer awareness towards GradHitz package offered by BIMB; and secondly, to identify the advertising tools that have been used by BIMB in order to promote the package to the consumers. Advertisement represents an important means of how an organization interacts with their customers both current and potential. It also enhances company performance besides making the entire consumer aware about the offered products. In this study, the most influential advertisement tools as what have been applied by the BIMB will be identified. The scope of study was confined to the BIMB walk in consumer at Darul Takaful building in Jalan Sultan Ismail, Kuala Lumpur. The researcher used descriptive research as the research design and the sampling technique is nonprobability. Convenience sampling was chosen in order to distribute 100 questionnaires. From the study, it has been identified that the majority of the consumers were aware of the GradHitz package offered. BIMB have advertised the GradHitz package via newspaper, brochures, bunting, glass door stickers and websites. However, the newspaper has been identified as the most influential tool in which BIMB should use more frequently in the future.